Respuesta :
Important: to denote exponentiation use " ^ ":
(x + y)1 = ___ x + ___ y NO
(x + y)^1 = ___ x + ___ y YES
(x+y)^1 = 1x + 1y
(x+y)^2 = 1x + 2xy + y^2
(x+y)^3 = 1x^3 + 3x^2*y + 3x*y^2 + y^3
and so on. Look up "Pascal's Triangle" if you want more info on this pattern.
*******************
(x + y)4 = ___ x4 + ___ x3y + ___ x2y2 + ___ xy3 + ___ y4 NO
(x + y)^4 = ___ x^4 + ___ x^3y + ___ x^2y^2 + ___ xy^3 + ___ y^4 YES
(x+y)^4 = 1x^4 + 4x^3*y + 6x^2*y^2 + 4x*y^3 + y^4
(x + y)1 = ___ x + ___ y NO
(x + y)^1 = ___ x + ___ y YES
(x+y)^1 = 1x + 1y
(x+y)^2 = 1x + 2xy + y^2
(x+y)^3 = 1x^3 + 3x^2*y + 3x*y^2 + y^3
and so on. Look up "Pascal's Triangle" if you want more info on this pattern.
*******************
(x + y)4 = ___ x4 + ___ x3y + ___ x2y2 + ___ xy3 + ___ y4 NO
(x + y)^4 = ___ x^4 + ___ x^3y + ___ x^2y^2 + ___ xy^3 + ___ y^4 YES
(x+y)^4 = 1x^4 + 4x^3*y + 6x^2*y^2 + 4x*y^3 + y^4
Answer:
[tex]a_0=1, a_1=1[/tex]
[tex]a_2=1, a_3=2,a_4=1[/tex]
[tex]a_5=1,a_6= 3,a_7=3,a_8=1[/tex]
[tex]a_9=1,a_1_0=4,a_1_1=6,a_1_2=4,a_1_3=1[/tex].
Step-by-step explanation:
[tex](x+y)^1=\binom{1}{0}x+ \binom{1}{1}y[/tex]
[tex]\binom{n}{r}=\frac{n!}{r!(n-r)!}[/tex]
Expansion:[tex](x+y)^n=a_0x^n+a_1x^{n-1}y+a_2x^{n-2}y^2+...............a_ny^n[/tex]
then we get
[tex](x+y)^1= x+y[/tex]
Therefore, we get [tex]a_0=1,a_1=1[/tex]
[tex](x+y)^2=\binom{2}{0}x^2+\binom{2}{1}xy+\binom{2}{2}y^2[/tex]
[tex](x+y)^2=x^2+2xy+y^2[/tex]
Therefore,[tex]a_2=1,a_3=2,a_4=1[/tex]
[tex](x+y)^3=\binom{3}{0}x^3+\binom{3}{1}x^2y+\binom{3}{2}xy^2+\binom{3}{3}y^3[/tex]
[tex](x+y)^3=x^3+ 3x^2y+3xy^2+y^3[/tex]
Therefore, [tex]a-5=1,a_6=3,a_7=3,a_8=1[/tex]
[tex](x+y)^4=\binom{4}{0}x^4+\binom{4}{1}x^3y+\binom{4}{2}x^2y^2+\binom{4}{3}xy^3+\binom{4}{4}y^4[/tex]
[tex](x+y)^4=x^4+4x^3y+6x^2y^2+4xy^3+y^4[/tex]
Therefore, [tex]a_9=1,a_1_0=4,a_1_1=6,a_1_2=4,a_1_3=1[/tex].